The Job Search Behavior of Employed Youth - Parsons, Donald O. (The Review of Economics and Statistics, 1991)
An employed worker's search strategies include (1) employed-not searching, (2) employed-searching, and (3) unemployed-searching. The last requires that the worker quit to search. Under plausible assumptions on search costs, the optimal algorithm involves a dual reservation wage strategy (Burdett, 1978). The probability of on-the-job search increases as the current wage decreases relative to the distribution of alternative wages. If the wage is sufficiently low, the searcher quits to search, substituting time for financial outlays. Estimates based on the National Longitudinal Survey of Youth indicate that these calculations characterize the search strategies of young workers. Copyright 1991 by MIT Press.